Hubungan Resiliensi Akademik dan Dukungan Sosial dengan Prokrastinasi Akademik pada Mahasiswa Angkatan 2015 Dan 2016 Fakultas Psikologi Universitas Medan Area - Dewi Shinta; Risydah Fadilah; Abdul Murad (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
The purpose of this study was to examine the correlation between academic resilience and social support with academic procrastination of College Students Faculty Of Psychology batch 2015 and 2016, Medan Area University. The approach used in this study was a quantitative approach . The samples technique in this study was an accidental sampling. In this study, the researcher used three scale measuring as the instrument type. The scale used to measure the academic procrastination, academic resilience and social support. The data analysis techniques used in this study was a multiple regression analysis. Based on the analysis of data the results show that: (i). There was a negative significant correlation between academic resilience with academic procrastination which was seen from R= -0,885 and R2=0,784 where p < 0.05. (ii). There was a negative significant correlation between social support with academic procrastination which was seen from R= -0,454 and R2=0,206 where p < 0.05. (iii). There was a significant correlation between academic resilience and social support with academic procrastination which was seen from coefficient F value = 218,390 and p<0,050 . It means that there was a significant correlation academic resilience and social support with academic procrastination college students Faculty Of Psychology batch 2015 and 2016, Medan Area University.